Agrimonia eupatoria L. Aqueous Extract Improves Skin Wound Healing: An In Vitro Study in Fibroblasts and Keratinocytes and In Vivo Study in Rats - Vasilenko, Tomáš; Kováč, Ivan; Slezák, Martin; Ďurkáč, Ján; Peržel'ová, Vlasta; Čoma, Matúš; Kaňuchová, Miriam; Urban, Lukáš; Szabo, Pavol; Dvořánková, Barbora; Vrzgula, Andrej; Zajíček, Robert; et al. (In vivo (Athens, Greece), 2022)
BACKGROUND/AIM: We have previously shown that the water extract of Agrimonia eupatoria L. (AE) is a valuable source of polyphenols with excellent antioxidant properties and has clinical potential for the prevention and/or adjuvant therapy of cardiovascular complications associated with diabetes. Inspired by our previously published data, in the present study we examined whether AE improves skin wound healing in a series of in vitro and in vivo experiments. MATERIALS AND METHODS: In detail, we investigated the ability of the AE extract to induce fibroblast to myofibroblast conversion, extracellular matrix (ECM) deposition, and keratinocyte proliferation/differentiation, in vitro. In parallel, in an animal model, we measured wound tensile strength (TS) and assessed the progression of open wounds using basic histology and immunofluorescence. RESULTS: The AE extract induced the myofibroblast-like phenotype and enhanced ECM deposition, both in vitro and in vivo. Furthermore, the wound TS of skin incisions and the contraction rates of open excisions were significantly increased in the AE-treated group. CONCLUSION: The present data show that AE water extract significantly improves the healing of open and sutured skin wounds. Therefore, our data warrant further testing in animal models that are physiologically and evolutionarily closer to humans.
Keywords: Animals; keratinocyty; extracellular matrix; Agrimonia; Keratinocytes; Fibroblasts; Skin tissue; rostlinné extrakty; Wound Healing; phytotherapy; fibroblasty; repair; voda; Water; modely nemocí na zvířatech; Disease Models, Animal; Plant Extracts; hojení ran; krysa rodu Rattus; regeneration; zvířata; Rats